Real‐life experience of tolvaptan use in the treatment of severe hyponatraemia due to syndrome of inappropriate antidiuretic hormone secretion. (3rd November 2015) - Tzoulis, Ploutarchos; Waung, Julian A.; Bagkeris, Emmanouil; Carr, Helen; Khoo, Bernard; Cohen, Mark; Bouloux, Pierre Marc
Summary: Objective: European guidelines do not recommend tolvaptan for treatment of syndrome of inappropriate antidiuretic hormone secretion (SIADH), principally owing to concerns about risk of overly rapid correction of hyponatraemia. This study evaluated the real‐life effectiveness and safety of tolvaptan. Design: Consecutive case series. Patients: Inpatients treated with tolvaptan for SIADH in 2 UK hospitals over a 3‐year period. Measurements: The primary outcome measures were serum sodium (sNa) correction at 24 and 48 h after tolvaptan therapy. Results: This case series included 61 patients aged 74·4 ± 15·3 years with (mean ± SD) sNa 119·9 ± 5·5 mmol/l. The mean sNa increase 24 h after tolvaptan initiation was 9 ± 3·9 mmol/l. Excessive correction of hyponatraemia was observed in 23% of patients with all these patients having baseline sNa <125 mmol/l, but no cases of osmotic demyelination syndrome were recorded. At the end of tolvaptan therapy, sNa increase was 13·5 ± 5·9 mmol/l with 96·7% of patients having sNa increase ≥5 mmol/l in 48 h. There was a negative significant correlation ( P = 0·012) between baseline sNa and 24‐h change; for every 1 mmol/l reduction in baseline value, sNa increased by an additional 0·23 mmol/l (95% CI 0·05–0·41). Conclusions: Tolvaptan is effective in correcting hyponatraemia. Without rigorous electrolyte monitoring, tolvaptan carries a significant risk of overly rapid sodium correction, especially in patients with starting sNa <125 mmol/l. Tolvaptan should be used with great caution under close electrolyte monitoring.